2018
DOI: 10.1016/j.rmed.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Mucus hypersecretion in asthma is associated with rhinosinusitis, polyps and exacerbations

Abstract: Mucus hypersecretion is frequent in patients with asthma, and is associated with chronic upper airways disease, airway obstruction, poor asthma control and more exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 31 publications
4
14
1
1
Order By: Relevance
“…Our ndings point to clinical characteristics that differentiate patients with and without mucus hypersecretion, mainly that hypersecretors are older, have severer asthma, greater bronchial obstruction and poorer asthma control, have lower peripheral blood albumin and lower IgE levels, have lower induced sputum lymphocyte levels, are less likely to have prick test-positive asthma and, nally, needed more short-term oral glucocorticoid treatments in the previous year. Our results corroborate those of Martínez-Rivera et al (28), who reported that hypersecretion, common in patients with asthma, was associated with greater airway obstruction, poorer asthma control and more exacerbation episodes. Another European prospective respiratory health study followed up over 9 years reported that one determinant of asthma severity was airway mucus hypersecretion (29).…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings point to clinical characteristics that differentiate patients with and without mucus hypersecretion, mainly that hypersecretors are older, have severer asthma, greater bronchial obstruction and poorer asthma control, have lower peripheral blood albumin and lower IgE levels, have lower induced sputum lymphocyte levels, are less likely to have prick test-positive asthma and, nally, needed more short-term oral glucocorticoid treatments in the previous year. Our results corroborate those of Martínez-Rivera et al (28), who reported that hypersecretion, common in patients with asthma, was associated with greater airway obstruction, poorer asthma control and more exacerbation episodes. Another European prospective respiratory health study followed up over 9 years reported that one determinant of asthma severity was airway mucus hypersecretion (29).…”
Section: Discussionsupporting
confidence: 92%
“…One of the important features of asthma is the mucus deposition and alterations in bronchial epithelia. Moreover, mucus production usually affects nasal epithelia and it is known that rhinitis is strongly associated to the development and the worsening of asthma symptoms [45]. OVA inhalation induces mucus deposition in airway epithelial cells, which is positively correlated with the reduction in lung function [46].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with asthma, mucous hypersecretion is associated with more symptoms, more obstruction, and more exacerbations. 61 Furthermore, in this case, roflumilast has revealed improvement of symptoms and lung function in asthmatics when added to montelukast, in comparison to this drug used in monotherapy. 62 …”
Section: Therapeutic Goals and Treatable Traits In Cadmentioning
confidence: 72%